PENERAPAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE BERBANTUAN POWER POINT INTERAKTIF PADA PEMBELAJARAN IPAS SISWA KELAS IV SD NEGERI 85 LUBUKLINGGAU - Sanda Dwi Putri A; Akmal Rijal, Akmal Rijal; Dea Widaswari, Dea Widaswari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the achievement of IPAS learning outcomes among This study aims to determine the improvement in Mathematics learning outcomes of fourth-grade students of SD Negeri 85 LubukLinggau after using the Inside Outside Circle learning model Assisted by Interactive Power Point. This study uses Pre-test and Post-test. Sampling was obtained from the population, the sampling technique in this study was using random sampling. The instrument used was in the form of multiple choices totaling 17 questions. The data analysis technique used the z-test at a significance level of a = 0.05. The results of the study obtained that z count = 5.11 > z table = 1.64 so that it is proven that Ha is accepted and Ho is rejected the improvement in Science learning outcomes of fourth-grade students of SD Negeri 85 LubukLinggau after using the Inside Outside Circle learning model was significantly complete. The average value was 80.63 and the percentage of students who completed was 91.66%.